SERUM CREATINE KINASE LEVEL IN SUDANESE PATIENTS WITH LONG STANDING DIABETES MELLITUS TYPE 2 IN KHARTOUM STATE, CENTRAL SUDAN - Awadalla, Akram H.; Elabid, Bader Eldien; Alzubeir, Maysoon (Gezira Journal of Health Sciences; Vol 6 No 1 (2010), 2010)
Objectives: To evaluate and correlate the serum activity of creatine kinase in Sudanese patients with type 2 long standing diabetes mellitus. Patients, Materials and Methods: This is a prospective, descriptive, cross- sectional, hospital based, case- control study was done in fifty patients (Twenty male &thirty female) above forty years with long period diabetes mellitus type 2 referred to Jabber Abu Eliz Diabetes Center and Bahri Diabetes Center in Khartoum state in central Sudan during May – October 2007. Thirty healthy volunteers with matching age and sex and socioeconomic status were included. Data was collected through, clinical evaluation form, questionnaire, and laboratory investigations. Serum concentrations of creatinine kinase were measured by spectrophotometery and t. test and correlation were used in statistical analysis for the comparison between test and control group. Results: The result showed a significant difference between the mean of serum creatine kinase of the control group compared with that of the case group (Mean±SD): (58.02±12.3); (90.46±47.6) U/L respectively, (P<0.05). Also there was a weak positive correlation (r) = 0.40, P =0.01 between the serum levels of  creatine kinase and the duration of diabetes mellitus Conclusion: From this study it was concluded that; the increase of the serum levels of creatine kinase may be due to the damage of cardiac or skeletal muscles, so this study recommends the measurment of creatine kinase isoenzymes for differentiation.